Optimization of Pura Keraban Langit's Infrastructure through the Community Service Program: Planning of Fencing, Retaining Wall Foundations, and Parking Area: Optimalisasi Infrastruktur Pura Keraban Langit melalui Program Pengabdian kepada Masyarakat (PKM): Perencanaan Pagar, Pondasi Penahan Tanah, dan Area Parkir - Silvi, Ni Putu; I Gede Gandhi Silantara (Universitas Lancang Kuning, 2025)
This Community Service (PkM) was carried out by lecturers from the Faculty of Science and Technology, Ngurah Rai University with the aim of improving the infrastructure of Keraban Langit Temple through the planning of wall fences, retaining foundations, and parking areas. The methods used include field surveys, measurements, infrastructure design with AutoCAD. The results are in the form of technical designs that support the aesthetics of Balinese culture and improve the security and comfort of the temple. This program supports the preservation of local cultural heritage while strengthening academic and community collaboration. The results of this PkM are in the form of a design drawing of a wall fence with a length of 80.9 m and a height of 1.75 m, a plan for a retaining foundation with a length of 38 m and a height of 0.8 m, and a plan for installing paving in a parking area with an area of ​​213.5 m2. Thus, with PkM, accessibility, security, and comfort can be improved, with an aesthetic traditional Balinese fence design and a stable retaining foundation. This program not only supports the preservation of local culture but also creates a model of collaboration between academics and the community for the development of sustainable infrastructure.